2021
DOI: 10.3390/pathogens10081005
|View full text |Cite
|
Sign up to set email alerts
|

Four Tick-Borne Microorganisms and Their Prevalence in Hyalomma Ticks Collected from Livestock in United Arab Emirates

Abstract: Ticks and associated tick-borne diseases in livestock remain a major threat to the health of animals and people worldwide. However, in the United Arab Emirates (UAE), very few studies have been conducted on tick-borne microorganisms thus far. The purpose of this cross-sectional DNA-based study was to assess the presence and prevalence of tick-borne Francisella sp., Rickettsia sp., and piroplasmids in ticks infesting livestock, and to estimate their infection rates. A total of 562 tick samples were collected fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 52 publications
1
17
1
Order By: Relevance
“…This tick is the competent vector of CCHF [49] and poses a serious threat to livestock, as well as humans, who may be exposed to tick bites in the livestock industry. In the UAE, this species was found to be a carrier of CCHF [7], T. annulata and Theileria ovis [50].…”
Section: Discussionmentioning
confidence: 97%
“…This tick is the competent vector of CCHF [49] and poses a serious threat to livestock, as well as humans, who may be exposed to tick bites in the livestock industry. In the UAE, this species was found to be a carrier of CCHF [7], T. annulata and Theileria ovis [50].…”
Section: Discussionmentioning
confidence: 97%
“…FLEs are assumed to be non-pathogenic to humans, though they may cause limited pathogenicity in small animals ( Keim et al, 2007 ) and are found in human-biting ticks, including those belonging to the genera Dermacentor , Amblyomma , Ixodes , and Hyalomma ( Scoles, 2004 ; Machado-Ferreira et al, 2009 ; Ivanov et al, 2011 ; de Carvalho et al, 2016 ; Azagi et al, 2017 ). Presence of the genus Francisella has been reported in the camel tick, Hyalomma dromedarii , through 16s rRNA sequencing, with high relative abundance (99%) ( Perveen et al, 2020b ) and subsequent PCR confirming close relation to FLE ( Perveen et al, 2021a ). In the same geographic area, H. dromedarii ticks were reported throughout the year with high prevalence (94%) ( Perveen et al, 2020a ).…”
Section: Impact Of Symbionts On Tick Physiologymentioning
confidence: 91%
“…As a taxonomic group, ticks are well-adapted to a wide range of climatic conditions, thriving in tropical, temperate and even subarctic habitats ( Anderson and Magnarelli, 2008 ). Ticks (Acari: Ixodida) are divided into three families: Ixodidae, Argasidae, and Nuttalliellidea ( Anderson and Magnarelli, 2008 ; Perveen, 2021 ), and almost 28 tick species have been reported to transmit pathogens to humans ( Anderson and Magnarelli, 2008 ). The prevalence of many tick-borne pathogens, such as Babesia , Theileria , and Borrelia has increased in recent years due to climate change and other anthropogenic factors such as land use change, deforestation, urbanization, global travel, and trade ( Rochlin and Toledo, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Hyalomma anatolicum , a widely distributed tick species that occurs worldwide, is the main vector of piroplasmids, including Theileria annulata , T. lestoquardi , T. equi and Babesia caballi , as well as Crimean-Congo hemorrhagic fever virus [ 4 ]. In a recent study, H. anatolicum in the United Arab Emirates (UAE) was found to be infected with T. annulata and Theileria ovis [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have been carried out on the microbiome of ticks infesting livestock [ 6 , 18 , 19 ]. In the UAE, ticks are a continuous problem in livestock [ 5 ], particularly in camels. In a study conducted in 2019–2020, the camel tick, Hyalomma dromedarii , was found on camels throughout the year [ 20 ].…”
Section: Introductionmentioning
confidence: 99%